Analysis of Risk Factor Assessment that Contributes to the Incidence of Work Stress among Employees in Purwakarta Regency, Indonesia - Auliawati, Nur (HM Publisher, 2024)
Work stress is a condition that is often experienced by employees in various industrial sectors. This study aims to analyze risk factors that contribute to the incidence of work stress in employees in Purwakarta Regency, Indonesia. The design of this research is observational analytic with a cross-sectional approach. Data was collected from 384 employees using a standard work stress questionnaire and analyzed using logistic regression. The results of the study show that the risk factors that contribute to the incidence of work stress among employees in Purwakarta Regency are workload (OR = 2.35; 95% CI: 1.25-4.42), interpersonal relationships in the workplace (OR = 2, 01; 95% CI: 1.10-3.70), and dual role (OR = 1.82; 95% CI: 1.02-3.27). In conclusion, workload, interpersonal relationships at work, and multiple roles are risk factors that contribute to the incidence of work stress among employees in Purwakarta Regency.